2021
DOI: 10.1016/j.celrep.2021.109627
|View full text |Cite
|
Sign up to set email alerts
|

One-shot identification of SARS-CoV-2 S RBD escape mutants using yeast screening

Abstract: The potential emergence of SARS-CoV-2 Spike (S) escape mutants is a threat to reduce the efficacy of existing vaccines and neutralizing antibody (nAb) therapies. An understanding of the antibody/S escape mutation landscape is urgently needed to preemptively address this threat. Here we describe a rapid method to identify escape mutants for nAbs targeting the S receptor binding site. We identified escape mutants for five nAbs, including three from the public germline class VH3-53 elicited by natural COVID-19 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 48 publications
5
55
0
Order By: Relevance
“…6 B, 7 B, and Fig. S12 , Table 2 and Table S20 ), in line with recent findings 78 . Finally, and in full agreement with Lilly’s data, LY-CoV016 is also found to be escaped by all spike N460 variations (N460I/K/S/T) (Figs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6 B, 7 B, and Fig. S12 , Table 2 and Table S20 ), in line with recent findings 78 . Finally, and in full agreement with Lilly’s data, LY-CoV016 is also found to be escaped by all spike N460 variations (N460I/K/S/T) (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the alternative LY-CoV016 mAb, the official Lilly’s fact sheet 58 reports that SARS-CoV-2 spike mutants showing reduced susceptibility to etesevimab include substitutions K417N, D420N, and N460K/S/T. In agreement with this and other evidences 71 78 , our current computational alanine/mutagenesis study marks K417 and all its reported variants (K417E/N/R/T) as the strongest hot spots in eliciting potential escape to the LY-CoV016 mAb (Figs. 5 B, 6 A, 7 A, and Fig.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“… 1 Understanding the structural, functional, and mechanistic basis of such noncovalent protein–protein interactions can help rationalize emergent cellular behavior, 1 can be exploited for design of biologics like antibodies 2 and can also be used to map and predict the next moves in the trench warfare between humoral immunity and pathogen evasion and evolution. 3 …”
Section: Introductionmentioning
confidence: 99%
“… 26,61,62 Finally, the Whitehead group has developed a method to determine the set of mutations on S RBD which can escape monoclonal antibody neutralization. 3 …”
Section: Introductionmentioning
confidence: 99%